The Relationship between Axis Length Difference and Refractive Error in Unilateral Myopic Anisometropic Children Treated with Orthokeratology - Lu Sun; Zheng-Xuan Li; Shi-Peng Wang; Hong-Xin Song (Journal of Ophthalmology)
Purpose. To explore the correlation between the axial length (AL) difference (myopic and nonmyopic eye) and the refractive error in children with unilateral myopia anisometropia (UMA) and to elucidate its clinical application in the process of Ortho-K lenses review following nonstop wearing. Methods. This study retrospectively analyzed the data of 70 children with UMA (age, 8–15 years) whose myopic eyes were treated with Ortho-K lenses. The spherical equivalent refractive errors (SERE) of the myopic eye ranged from −0.75 D to −4.25 D, and astigmatism was no less than −1.50 D. In addition, SERE of nonmyopic eyes were no less than −0.50 D. AL, and the refractive data of both eyes were measured at baseline. A multivariate linear regression was used to analyze the relationship between the AL difference and refractive error, and paired t-test was used to analyze the changes in AL in both eyes. Results. Every 1 mm axial length change corresponds to −1.627 D (95% CI: −1.921 D, −1.333 D; P<0.001) change in refractive error in children. The association between the AL change and the degree of myopia did not change with age (P=0.751). Among the 70 subjects, 51 (72.86%) had myopia in the right eye, and the 95% confidence interval (CI) for myopia occurring in the right eye was 62.4%–83.3%. The paired t-test showed that the average AL growth was significantly slower in myopic eyes treated with Ortho-K lenses than in nonmyopic eyes (t = 9.805, P<0.001). Conclusion. Every 1 mm AL change would cause an average refractive error increase. Age did not influence the association between AL changes and the degree of myopia. The right eye is more likely to be affected in children with UMA. The Ortho-K lens treatment slowed down the growth of AL in the myopic eye in children with UMA.